2021
DOI: 10.1039/d1ma00769f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in silver nanoparticle-based electrochemical sensors for determining organic pollutants in water: a review

Abstract: Water pollutants have attracted a great attention because their negative effect on human health. Accordingly, various analytical techniques were investigated to detect the water pollutants as a preliminary step for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 174 publications
0
41
0
Order By: Relevance
“…It could be observed that the cathodic peak was clear at all investigated concentrations of HMF and the measured cathodic current sharply improved with the increase in the molarity of HMF in the supporting electrolyte. AgNP-modified electrodes are known for their increased electroactive surface area and superior conductivity compared with unmodified electrodes [ 59 ]. They can detect various inorganic and organic analytes on the basis of the electrochemical responses of AgNPs [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…It could be observed that the cathodic peak was clear at all investigated concentrations of HMF and the measured cathodic current sharply improved with the increase in the molarity of HMF in the supporting electrolyte. AgNP-modified electrodes are known for their increased electroactive surface area and superior conductivity compared with unmodified electrodes [ 59 ]. They can detect various inorganic and organic analytes on the basis of the electrochemical responses of AgNPs [ 60 , 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The selection of functional electrode-modifying material may overcome the common analytical problems of bare electrodes, such as electrode fouling and overlapping of the redox-potential in the simultaneous determination of multiple analytes. In this context, silver nanoparticles (AgNPs) are one of the most relevant and frequently used materials for the development of versatile electrochemical sensing platforms due to their unique physicochemical properties [ 13 ]. AgNPs can be produced in an easy and cost-effective way with various morphologies, have an adjustable architecture, and are stable at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large number of review articles have been reported regarding nanomaterial-enhanced electrochemical devices for monitoring various pollutants in the aquatic environments—heavy metals [ 31 ], chemicals [ 32 ], organic molecules [ 13 ], nutrients [ 33 ], nitrites and nitrates [ 8 ], and pharmaceuticals [ 4 ]—providing a broad survey through the field of nanosilver-based sensing platforms. This can be evidenced by the exponential growth in the number of scientific papers implementing nanosilver particles for the development of electrochemical sensors in the period of the last twenty years (determined by searching the WoS platform using the keywords electrochemical* (title) AND *silver OR Ag AND *nano AND environmental*; Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Dai et al introduced the concept of re-creation of the existing platforms, which transferred the NPs-based colorimetric assay into the electrochemical analysis with Hg 2+ as the model analyte [28]. After that, a number of attempts have been put into the construction of various detection techniques based on the conversion of aggregation-based colorimetirc assays to interfacial analytical assays [29][30][31][32][33]. In addition to acting as the aggregation triggers, biomacromolecules with nanoscale sizes can also be used as the self-assembling building blocks to form diverse nanostructures for drug delivery and biosensing.…”
Section: Introductionmentioning
confidence: 99%